Evidence for differential effects of hepcidin in macrophages and intestinal epithelial cells. Issue 3 (26th October 2007) - Chaston, T; Chung, B; Mascarenhas, M; Marks, J; Patel, B; Srai, S K; Sharp, P
Abstract : Background and aims: Reticulo-endothelial macrophages together with duodenal enterocytes coordinate body iron homeostasis. The aim of this study was to investigate the regulatory actions of the hormone hepcidin on ferroportin expression in these two cell types. Methods: We investigated the in vitro effects of hepcidin in well-characterised human cell culture models of macrophages (differentiated THP-1 cells) and intestinal epithelial cells (Caco-2 cells). The in vivo effects of hepcidin were also investigated in mice injected with a synthetic hepcidin peptide. Results: Exposure to hepcidin (presented either as conditioned medium from interleukin-6-stimulated HuH7 cells or as a synthetic peptide) resulted in a rapid (within 4 h) decrease in ferroportin expression in THP-1 macrophages but had no effect on ferroportin levels in Caco-2 cells. To determine whether these rapid effects of hepcidin were also evident in vivo we injected mice with a synthetic hepcidin peptide. Four hours post-injection, ferroportin levels in the macrophage-rich red pulp of the spleen were decreased significantly and the hepcidin-treated mice developed hypoferraemia. Interestingly, in the same mice there was no effect of hepcidin on duodenal ferroportin protein expression or duodenal iron transport. Conclusions: These data suggests that the rapid response to hepcidin is cell type and tissue specific. Upon its release, hepcidin initially targets macrophage iron recycling. The duodenum appears to be less sensitive to this initial rise in hepcidin levels. We believe the fact that macrophages respond more acutely to a hepcidin challenge is fully consistent with their central role in maintaining body iron homeostasis.